A Note on Quotient Ternary Semirings and Isomorphism Theorems (European Journal of Pure and Applied Mathematics, 2025)
In this paper, we present a variety of notions of quotient ternary semirings, along with examples and remarks. Moreover, we establish various  isomorphism theorems for ternary semirings.
Keywords: $Q$-ideals; congruences; $k$-ideals; quotient ternary semirings; isomorphism Theorems